Unsur Keteladanan Tokoh dalam Buku Digital H.B. Jassin: Perawat Sastra Indonesia sebagai Bahan Ajar Bahasa Indonesia - Etikasari, Dian; Mulyaningtyas, Rahmawati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The younger generation possess problems in recognizing the national figures who have contributed greatly to the Indonesian nation. The Ministry of Education and Culture by its digital library releases the site budi.kemdikbud.go.id which provides the books that are very useful for children in recognizing Indonesian national figures. One of the books is entitled H.B Jassin: Perawat Sastra Indonesia which contains about the ins and outs of H.B Jassin that gives a great role model. This can be used as a role model for children in building their character development. In addition, the digital book H.B Jassin: Perawat Sastra Indonesia can be used as a teaching material for Indonesian language learning. The purpose of this research is to describe the noble attitude of H.B Jassin and the use of the digital book H.B Jassin: Perawat Sastra Indonesia as Indonesian language teaching material. Descriptive qualitative was chosen as the research method an digital book H.B Jassin: Perawat Sastra Indonesia as the source data. From the results of the analysis, it was found that the noble character elements of H.B. Jassin, they are fond of reading, passionate and brave, confident, devoted to parents, respectful, diligent and thorough, honest and responsible, persistent, charitable, humble, simple, patient, forgiving, creative, hardworking, religious, and nationalist person. Then, the digital book H.B Jassin: Perawat Sastra Indonesia is used as a teaching material for Indonesian language learning at the high school level in grade X at basic competencies 3.14 menilai hal yang dapat diteladani dari teks biografi.